Clinical Correlates of the Severity of Diabetic Foot Ulcers - Rahadyan Magetsari; Meirizal Hasan; Yossie Atyandhari (Journal of Global Pharma Technology, 2020)
OBJECTIVE Severe diabetic foot ulcer leads to amputation and is associated with higher risk of mortality. The purpose of this study is to identify clinical correlates of severe diabetic foot ulcers. METHODS The design of the study was cross-sectional survey of medical records on patients treated in Sardjito Hospital from 1 January to 31 July, 2014. Severe foot ulcer was measured as grade 4 and 5 according to Wagner classification. ABI (Ankle Brachial Index) to estimate blood flow to lower extremities and Semmes-Weinstein test using monofilament to detect neuropathy, classified as positive or negative, were done in all patients. HbA1C, serum sodium and creatinine levels were measured during the latest hospital visit. RESULTS The results of this study showed that 77 (36.5%) among 211 patients had severe foot ulcers (grade 4 and 5, Wagner classification). ABI and Semmes-Weinstein monofilament test failed to predict severity of diabetic foot ulcers. HbA1c increased the odds of severe ulcers while higher serum sodium level and higher diastolic blood pressure protected patients against severe ulcers. CONCLUSION Better glycemic control and caution against excessive reduction of diastolic blood pressure, usually due to anti-hypertension medication, should be recommended to prevent the development of severe foot ulcer. KEYWORDS: diabetic foot ulcers, severity, glycemic control, hypertension, poor circulation, neuropathy